Color code method design evaluation and data analysis - Dzelzkaleja, Laura (International Journal of Engineering and Technology, 2018)
Nowadays, with the growing attention to Educational data mining, it important to use the data analysis results to improve course assessment and improve the e-learning process. A new Color code method for understanding students’ learning process has been introduced in the previous research. The method uses three color codes: red for "problem", yellow for "work in progress" and green for "job done". The method has proven to work in a classroom environment and recently implemented in the edX learning platform. In this paper the button design is tested in four student groups and the button press data analyzed taking into consideration students’ gender and exam marks. Research show that 18% of the students used buttons without difference in gender and that highest button usage activity had the least course non-finishers and the highest number of students that got the highest mark. Survey showed that button design needs some improvement.